2019
DOI: 10.1007/978-3-030-10928-8_32
|View full text |Cite
|
Sign up to set email alerts
|

Mining Periodic Patterns with a MDL Criterion

Abstract: The quantity of event logs available is increasing rapidly, be they produced by industrial processes, computing systems, or life tracking, for instance. It is thus important to design effective ways to uncover the information they contain. Because event logs often record repetitive phenomena, mining periodic patterns is especially relevant when considering such data. Indeed, capturing such regularities is instrumental in providing condensed representations of the event sequences. We present an approach for min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…When adding a pattern to our model we search for the best possible refinement, that is we greedly extend our pattern to that version that gives us the highest gain in bits saved, we refer the reader to 'Appendix A.1' where we provide a more detailed explanation. After adding a pattern, we re-compute the residual (l. [13][14]. We repeat these steps until we have no further candidates (l. 3) and then return the final model M. In Fig.…”
Section: Algorithm 1: Omenmentioning
confidence: 99%
See 1 more Smart Citation
“…When adding a pattern to our model we search for the best possible refinement, that is we greedly extend our pattern to that version that gives us the highest gain in bits saved, we refer the reader to 'Appendix A.1' where we provide a more detailed explanation. After adding a pattern, we re-compute the residual (l. [13][14]. We repeat these steps until we have no further candidates (l. 3) and then return the final model M. In Fig.…”
Section: Algorithm 1: Omenmentioning
confidence: 99%
“…All use greedy search algorithms, iteratively adding patterns to a model until convergence. Galbrun et al [13] studied the problem of discovering sequential patterns with reliably periodically appear. Instead of taking a descriptive approach, Fowkes and Sutton [12] proposed a method to discover small sets of informative patterns based on a generative model.…”
Section: Related Workmentioning
confidence: 99%
“…However, descriptive approaches using pattern mining on time series data have been mostly neglected so far, as also discussed above. An approach for compressing event logs based on the minimum description length (MDL) principle was presented by [19], making it possible to detect local patterns in temporal data. Compared to this work, which focuses on event sequences, our approach aims to find meaningful representations of (potentially complex) continuous-valued recordings, and assesses the discovered patterns by reference to a target variable rather than compression.…”
Section: Exceptionality Detection In Time Seriesmentioning
confidence: 99%
“…given data). The MDL principle has been successfully employed to select descriptive sets of patterns from transactional databases [13], sequence databases [5,12], relational databases [8], geometric data [4], and graphs [1].…”
Section: The MDL Principlementioning
confidence: 99%
“…Several kinds of approaches have been proposed to tackle this problem (e.g., constraint based approaches [16] or condensed representation [15]). Among them, the methods based on the Minimum Description Length (MDL) principle demonstrated that it is possible to drastically reduce the number of patterns by selecting a small set of descriptive patterns among all the generated patterns [4,5,8,12,13]. The MDL principle [6] comes from information theory, and states that the model that describes the data the best is the one that compresses the data the best, i.e.…”
Section: Introductionmentioning
confidence: 99%